2019
DOI: 10.2209/tdcpublication.2018-0015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Liquid Based Cytology for Tongue Squamous Cell Carcinoma: Comparison with Conventional Cytology

Abstract: Oral exfoliative cytology is now used by general practitioners in Japan to screen for oral cancer. With conventional cytology, however, the number of cells that can be sampled is small. Moreover, cell deformation and piling of cells when preparing specimens has been reported. The purpose of this study was to compare conventional and liquid based cytology (LBC), which has been employed with increasing frequency in recent years. We believe that identifying potential pitfalls in oral exfoliative cytology will hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Previous OEC studies have shown that poor sampling may lead to a lower diagnostic accuracy. Generally, most dysplastic lesions arise in the basal and parabasal layer initially, and in most cases, the oral mucosa is well-differentiated superficially in the form of keratinization; therefore, the collection of deep-seated cells is crucial for accurate diagnosis using OEC [8,12]. However, low-grade lesions, especially those with strong keratinization, make collection of deepseated cells challenging [8,10,12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous OEC studies have shown that poor sampling may lead to a lower diagnostic accuracy. Generally, most dysplastic lesions arise in the basal and parabasal layer initially, and in most cases, the oral mucosa is well-differentiated superficially in the form of keratinization; therefore, the collection of deep-seated cells is crucial for accurate diagnosis using OEC [8,12]. However, low-grade lesions, especially those with strong keratinization, make collection of deepseated cells challenging [8,10,12].…”
Section: Discussionmentioning
confidence: 99%
“…There are many reports on the accuracy of OEC, including studies in high prevalence and high-grade populations. Generally, the accuracy of OEC was 70−90%, and the sensitivity and specificity were similar [1,[8][9][10]12,13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Liquid-based cytology (LBC) is a non-invasive technique that can be used for the early diagnosis of OSCC. LBC has higher diagnostic accuracy than conventional cytology; moreover, gene expression analysis and immunocytochemistry (ICC) can be performed on the residual LBC specimens ( 7 11 ). There are several reports on ICC and gene expression analysis; however, none of the studies have reported the continuous changes in morphology and the gene and protein expression during carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%